N-Terminal pro-Brain Natriuretic Peptide and Associations With Brain Magnetic Resonance Imaging (MRI) Features in Middle Age: The CARDIA Brain MRI Study - Ferguson, Ian T.; Elbejjani, Martine; Sabayan, Behnam; Jacobs, David R.; Meirelles, Osorio; Sanchez, Otto A.; Tracy, Russell; Bryan, Nick; Launer, Lenore J. (Frontiers in Neurology, 2018)
Objective As part of research on the heart–brain axis, we investigated the association of N-terminal pro-brain natriuretic peptide (NT-proBNP) with brain structure and function in a community-based cohort of middle-aged adults from the Brain Magnetic Resonance Imaging sub-study of the Coronary Artery Risk Development in Young Adults (CARDIA) Study. Approach and results In a cohort of 634 community-dwelling adults with a mean (range) age of 50.4 (46–52) years, we examined the cross-sectional association of NT-proBNP to total, gray (GM) and white matter (WM) volumes, abnormal WM load and WM integrity, and to cognitive function tests [the Digit Symbol Substitution Test (DSST), the Stroop test, and the Rey Auditory–Verbal Learning Test]. These associations were examined using linear regression models adjusted for demographic and cardiovascular risk factors and cardiac output. Higher NT-proBNP concentration was significantly associated with smaller GM volume (β = −3.44; 95% CI = −5.32, −0.53; p = 0.003), even after additionally adjusting for cardiac output (β = −2.93; 95% CI = −5.32, −0.53; p = 0.017). Higher NT-proBNP levels were also associated with lower DSST scores. NT-proBNP was not related to WM volume, WM integrity, or abnormal WM load. Conclusion In this middle-aged cohort, subclinical levels of NT-proBNP were related to brain function and specifically to GM and not WM measures, extending similar findings in older cohorts. Further research is warranted into biomarkers of cardiac dysfunction as a target for early markers of a brain at risk.